Association between the mannose-binding lectin (MBL)-2 gene variants and serum MBL with pulmonary tuberculosis: An update meta-analysis and systematic review. (July 2019) - Tong, Xiang; Wan, Qunfang; Li, Zhenzhen; Liu, Sitong; Huang, Jizhen; Wu, Man; Fan, Hong
Abstract: In recent years, many studies have demonstrated that the MBL-2 gene polymorphisms may be associated with pulmonary tuberculosis (PTB) susceptibility. Moreover, some studies have shown that serum MBL levels were influenced by the MBL-2 gene polymorphisms and that it plays an important role in tuberculosis infection. However, the results of these studies were inconsistent and underpowered. The current meta-analysis and systematic review aimed to evaluate the association between the MBL-2 gene polymorphisms and serum MBL levels with PTB. Finally, 30 eligible articles were included in the study. The overall results indicated that the MBL-2 rs1800450 (54 A/B) and rs5030737 (52 A/D) polymorphisms were risk factors for PTB, but the MBL-2 rs1800451 (57 A/C) and rs7095891 (+4 P/Q) polymorphisms as protective factors against PTB. No associations were found in the other three polymorphisms (exon 1, rs7096206 (−221 X/Y), and rs11003125 (−550 H/L) of the MBL-2 gene. In addition, we could not detect any significant differences between haplotypes among PTB patients and healthy controls. More important, the meta-analysis results indicated that the serum MBL levels in patients with PTB were significantly lower than those in healthy controls (SMD = 0.43, 95% CI = 0.33–0.52). This study suggested that the MBL-2 gene polymorphisms may be involved in the pathogenesis of PTB, and serum MBL may be a biomarker for the diagnosis of PTB. More rigorous research is needed in the future to confirm these findings further. Highlights: MBL-2 rs1800450 and rs5030737 polymorphisms may be risk factors for PTB. MBL-2 rs1800451 and rs7095891 polymorphisms may be protective factors against PTB. Serum MBL may be a biomarker for the diagnosis of PTB.